Neural Correlates of Causal Inferences and Semantic Priming in People with Williams Syndrome: An fMRI Study - Hsu, Ching-Fen (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
This study aimed at examining the ability of causal inferences and semantic priming of people with Williams syndrome (WS). Previous studies pointed out that people with WS showed deviant sentence comprehension, given advantageous lexical semantics. This study investigated the impairment in connecting words in the semantic network by using neuroimaging techniques to reveal neurological deficits in the contextual integration of people with Williams syndrome. Four types of word pairs were presented: causal, categorical, associative, and functional. Behavioural results revealed that causal word pairs required heavier cognitive processing than functional word pairs. Distinct neural correlates of semantic priming confirmed atypical semantic linkage and possible cause of impairment of contextual integration in people with WS. The findings of normal behaviours and atypical neural correlates in people with WS provide evidence of atypical development resulted from early gene mutations.